The correlation between color choices and impulsivity, anxiety and depression - Korkmaz, Sevda; Ozer, Omer; Kaya, Suheda; Kazgan, Asli; Atmaca, Murad (Modestum Ltd, 2016)
Objective: It is considered that, in addition to different effects of colors on mood, psychopathological processes are also a conductive factor in color preferences. Thus, the objective of the present study was to investigate whether there was a relationship between color preferences and impulsive behavior. Method: Socio-demographic information, anxiety levels, depression and impulsivity levels of 200 individuals aged 18-50, which were selected randomly, were assessed. Beck Anxiety (BAI), Beck Depression(BDI) and Barrat Impulsivity Scales(BIS) were applied to all participants. They were asked the first color that comes to mind and their favorite colors. Preferred colors were divided into three groups of cold (blue, purple, green), warm (red, yellow, pink, brown) and neutral colors (black, white, grey). Results: Study group included 87 males (43.5%), 113 females (56.5%) and their mean age was 26.9 +/- 6.2 years. (female mean age: 25.9 +/- 5.5; male mean age: 28.1 +/- 6.9). The first color that came to mind was blue (32%), followed by red (20%). Their most favorite colors were blue (33%) and black (20%). BIS total points were the highest for those who chose yellow, blue, purple and black colors, respectively. BAI was the highest in participants who preferred color black and BDI was the highest in participants who preferred color grey. Those who scored the highest points in BAI and BDI preferred neutral colors. Anxiety scores for those preferring cold, warm and neutral colors were statistically significantly different (p=0.02). Conclusion: Color preferences are closely related to impulsivity. Furthermore, anxiety and depression levels of individuals also affect their color preferences.
Keywords: Color; impulsivity; anxiety; depression